Personal data storage and management using error correction codes and elliptic curves proxy signature algorithm (Моделювання, керування та інформаційні технології, 2019)
Recently personal data storage and management have become one of the most important issues in the field of information technologies. 2018 was the year when well-known GDPR was issued which stated general personal data protection regulations. It’s very important to study methods and tools which can enhance the security of information systems processing personal data. Distributed data storages are widely used for fault tolerance as well as cryptography is used for access control.